Hook effect and serum KL-6 in Patients with Systemic Sclerosis-Associated Interstitial Lung Disease (SSc-ILD) - Emmy Hermiyanti Pranggono; Valentine Natasya Moenardi; Alvy Syukrie; Sumartini Dewi (Faculty of Medicine Universitas Padjadjaran, 2021)
Objective To determine whether serum KL-6 can be used as an alternative diagnostic tool for Systemic Sclerosis-associated ILD (SSc-ILD).Method This was a cross-sectional study with compatibility analysis of SSc patients visiting the rheumatology clinic of Dr. Hasan Sadikin General Hospital, Bandung, Indonesia in 2019-2020. Inclusion criteria were aged 18-60 years, diagnosed with SSc, restrictive spirometry results followed by HRCT thorax, having stored biological materials (<2 years) for serum KL-6 examination, and body mass index of <23 kg/m2. Patients with pneumonia, tuberculosis, history of tuberculosis, malignancy, and cardiac decompensation were excluded. Serum KL-6 level of >397.5 unit/mL was declared as ILD. The compatibility analysis was performed using the Cohen’s Kappa test.Results: Thirty-eight subjects, mostly women (94.7%), with mean age of 39 years participated in this study. Most of the subjects suffered from diffuse systemic sclerosis subtypes (57.9%). Subjects had received cyclophosphamide (10.5%), MMF (2.6%), and other medications. Almost all subjects (97.4%) demonstrated ILD features on HRCT thorax. The median serum KL-6 level was 53.22 Units/mL, which was much lower than the findings in other studies, but the hook effect could not be proven. The Kappa coefficient was found to be 0.003 with a p-value of 0.811.Conclusion There is no compatibility between serum KL-6 level and ILD features based on HRCT thorax in SSc-ILD. The presence of hook effect needs more attention.